Ferramenta Kaizen aplicada no laboratório de térmicas e fluídos da Universidade Federal Campus – Tucuruí - CAVALCANTE, Barbara Lima (2022)
This work is based on the methodology of Japanese origin, the Kaizen, in its turn is a strategic plan that over time, becomes incorporated into the routine, contributing to the achievement of total quality and having as an advantage the fact of causing changes behavioral in all responsible and users of the environment work and encourage the culture of discipline. Kaizen is an "umbrella" that covers all the improvement tools, so taking the maximum benefit that each one offers and allowing the adequacy to the different types of situation. Therefore, it consists in the execution of this methodology, at the Laboratory of Thermal and Fluids of the Federal University of Pará-Tucuruí Campus, the implementation of this work occurred with the use of the Brainstorming and 5S tools, these allow to organize a workplace to make it more efficient in quality and in productivity. Essentially, revitalizing the laboratory, adapting it to give the appropriate support to the mechanical engineering course and the Campus, since the university laboratories are much important to exercise the skills and to approximate the theoretical content of the reality for the student. The results of this study has evidenced an increase in the levels of quality, conservation of the environment and collection, more agility in the activities performed on the place, advances in the procedures, besides ensuring the safety and satisfaction of the users.